2015
DOI: 10.1021/acs.jpcc.5b02171
|View full text |Cite
|
Sign up to set email alerts
|

NMR and EPR Characterization of Functionalized Nanodiamonds

Abstract: We investigated the potential of solid-state NMR using magic angle spinning (MAS) with and without dynamic nuclear polarization (DNP) and electron paramagnetic resonance (EPR) for the characterization of functionalized nanodiamonds (NDs). We showed that conventional 1 H, 31 P, and 13 C solid-state NMR spectra allow differentiating in a straightforward way NDs from commercial sources and custom-made NDs bearing aromatic or aliphatic phosphonate moieties at their surface. Besides, the short nuclear relaxation ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 141 publications
(287 reference statements)
2
17
0
Order By: Relevance
“…As a consequence, the presence in the materials of paramagnetic centers, which do not contribute to the DNP transfer but shorten the electron and nuclear longitudinal relaxation times, T1(Si) and T1(I), respectively, decreases or even cancels the DNP enhancement. This polarization leakage phenomenon has been reported for materials containing endogeneous paramagnetic centers, such as natural clays and functional nanodiamonds [85,86]. Similarly, it has been shown that the removal of the paramagnetic molecular oxygen (O2) dissolved in organic solvents or adsorbed in polymers can improve the DNP enhancement [87,88].…”
Section: Dnp Mechanisms and Depolarizationmentioning
confidence: 58%
“…As a consequence, the presence in the materials of paramagnetic centers, which do not contribute to the DNP transfer but shorten the electron and nuclear longitudinal relaxation times, T1(Si) and T1(I), respectively, decreases or even cancels the DNP enhancement. This polarization leakage phenomenon has been reported for materials containing endogeneous paramagnetic centers, such as natural clays and functional nanodiamonds [85,86]. Similarly, it has been shown that the removal of the paramagnetic molecular oxygen (O2) dissolved in organic solvents or adsorbed in polymers can improve the DNP enhancement [87,88].…”
Section: Dnp Mechanisms and Depolarizationmentioning
confidence: 58%
“…Although the principles of this effect have been known for many decades, 2a , 3 its transposition to modern high-resolution NMR of solids at magnetic fields of 5 T or higher has become possible only relatively recently, with the introduction of gyrotron sources capable of delivering high-power high-frequency microwaves, 4 and of cryogenic MAS probes for experiments at 100 K or lower temperatures. In this respect, in the past few years, high-field MAS DNP-enhanced solid-state NMR spectroscopy has made great progress 5 and has been implemented successfully on a wide variety of systems, ranging from porous and non-porous materials, 6 colloids, 7 molecular organic solids including pharmaceuticals, 8 polymers, 9 membrane proteins, fibrillar aggregates, biomaterials or cells, 10 thus gaining more and more importance.…”
Section: Introductionmentioning
confidence: 99%
“…With all of the unique properties associated with nanodiamonds, they are truly a high impact material with a bright and opportunity filled future. [74], XPS [74], TDMS [75], NMR [74,76], Electrophoretic mobility (f potential) [75], Titration [77] Metal content (surface) PIXE, b ICP-MS [73,78,79] Diamond core Lattice quality XRD [73], HRTEM [ …”
Section: Future Outlookmentioning
confidence: 99%